The Influence of Social Media Marketing on Purchasing Decisions - Kurniadi, Wandi (Yayasan Pendidikan Belajar Berdikari, 2024)
Tokopedia was one of the earliest e-commerce mobile platforms in Southeast Asia, including Indonesia. With e-commerce rivalry, social media marketing on the Instagram platform is being utilized to attract new customers. As a result, this study was done to investigate the impact of social media marketing via electronic word of mouth on Tokopedia purchase choices using the Instagram platform. This study employs quantitative and descriptive research methodologies, with a sample size of 95 respondents. Non-probability sampling was employed, using the route analysis approach. Data was processed using SPSS version 25. The findings of this study indicate that social media marketing (X) has a large and influential impact on purchase choices